Pengembangan Media Pembelajaran Macromedia Flash 8 Untuk Meningkatkan Keterampilan Membaca Permulaan di Sekolah Dasar - Hidayah, Kurnia Nur; Zainil, Melva (Universitas Negeri Padang, 2024)
This research is motivated by the results of observations found in elementary schools that there has been no development of instructional media using the Macromedia Flash 8 application to improve initial reading skills in integrated thematic learning in grade II SD. This research is a Research & Development research with the ADDIE development model with the stages of analysis, design, development, implementation and evaluation. The results showed that: (1) the results of the validation test of learning media as a whole by three validators, namely aspects of material, language and media obtained with a very valid category, (2) the results of the practicality test of learning media by teachers and students in the very practical category, and (3) the results of the initial reading in the Very Good category. With cognitive levels adjusted to low class levels between C1, C2, and C3. Based on the results of the research that has been done, it can be concluded that the learning media using the Macromedia Flash 8 application are valid and practical to use in integrated thematic learning in class II elementary school.